1991
DOI: 10.1111/j.1600-0404.1991.tb04651.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrocorticography in temporal lobe epilepsy surgery

Abstract: The results of intra-operative cortical EEG recordings (ECoG) were assessed in 30 patients with medically refractory complex partial seizures submitted to temporal lobectomy. Interictal spiking was most frequently recorded from mesial temporal lobe structures (amygdaloid-hippocampal region) and from the temporal neocortex synchronously, as observed in 21/30 patients. In 7 patients, the interictal spiking involved the temporal neocortex exclusively. Electrical stimulation of mesial temporal lobe structures repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…In addition to the complexities already described with regard to individual discharges, most patients show more than one independent discharge pattern with distinct topographies regarding spike incidence, amplitude, sites with leading spikes and propagation patterns. The occurrence of multiple ECoG patterns with respect to amplitude and incidence of spikes has been described repeatedly (Engel et al, 1975;Graf et al, 1984;McBride et al, 1991;Stefan et al, 1991;Tsai et al, 1993a). Furthermore, we have found that most patients show more than one leading region with distinct associated propagation patterns.…”
Section: Neurophysiological Implicationssupporting
confidence: 61%
“…In addition to the complexities already described with regard to individual discharges, most patients show more than one independent discharge pattern with distinct topographies regarding spike incidence, amplitude, sites with leading spikes and propagation patterns. The occurrence of multiple ECoG patterns with respect to amplitude and incidence of spikes has been described repeatedly (Engel et al, 1975;Graf et al, 1984;McBride et al, 1991;Stefan et al, 1991;Tsai et al, 1993a). Furthermore, we have found that most patients show more than one leading region with distinct associated propagation patterns.…”
Section: Neurophysiological Implicationssupporting
confidence: 61%
“…Eigene Erfahrungen mit einzelnen Patienten während des Wada-Testes, bei denen es zum einen zu Weinausbrüchen und schweren depressiven Verstimmungen, zum anderen aber auch zu abnorm positiven Empfindungen und submanischem Verhalten kam, bestätigen diese Berichte. Ob bei diesen Patienten durch einen epilepsiechirurgischen Eingriff ähnliche dauerhafte Stimmungsänderungen auftreten ist nicht bekannt [13] (Tab. 2).…”
Section: Depression/traurigkeitunclassified
“…5 However, many others have failed to establish correlations between spike quantification and seizure outcome. [6][7][8][9][10] Despite its classical use in epilepsy surgery, most centers have abandoned intraoperative ECoG in cases of TLE-HS. However, ECoG analysis nowadays should probably include parameters other than post-resection spike quantification, in order to permit a more complete study of the pathophysiology of TLE, and in the search of patterns of prognostic value that could eventually influence the surgical technique.…”
Section: Introductionmentioning
confidence: 99%